(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2015)
The primary purpose of the study was to assess the extent of knowledge and perception of extension workers towards ICT utilization and to determine the relationship between the selected characteristics of the respondents and knowledge and perception of extension workers towards ICT utilization in extension service delivery. The study was conducted in Gazipur district and comprised proportionate random sample of 90 extension workers from five upazila of Gazipur district. A pre-tested interview schedule was used to collect data from the respondents. To measure the knowledge on ICT utilization 35 statements were selected regarding 7 ICT with five possible answer of each tools and a score of one was given to the right answer and zero to the wrong answer alternatively to measure the perception of the respondents rated each of 10 statements ICT utilization in agriculture on a 5-point Likert type scale and the total of these ratings formed perception index. The result of the study showed that out of seven ICT tools the knowledge of extension workers was highest in case of MS Word this was followed by internet/ web service and the lowest knowledge was found in case of Geographical Information System. It is observed that an overwhelming majority (88.9%) of agricultural extension workers in the study area had low to medium knowledge towards ICT utilization. Findings reveal that the respondents had top most perception on the ICT utilization in respect of Extension work can be greatly enhanced by ICT followed by on The benefits of ICT use outweigh the financial burden involved. The result also indicated that more than fourth-fifth (84.4%) of the respondents had medium to high perception towards ICT utilization. There were significant relationship between service experience and use of the information sources of the respondents with their knowledge towards ICT utilization conversely innovativeness, cosmopoliteness and job satisfaction of the respondents showed positive significant relationship with their perception towards ICT utilization. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22647 Int. J. Agril. Res. Innov. & Tech. 4 (2): 46-52, December, 2014